Simulation of long-term variations of the F2-layercritical frequency f0F2 at the northern tropical crest of ionization at Phu Thuy, Hanoi, Vietnam using the thermosphere-ionosphere-electrodynamicsgeneral circulation model (TIE-GCM) - Hong, Pham Thi Thu; Amory-Mazaudier, C.; Minh, Le Huy (Vietnam Journal of Earth Sciences, 2014)
In this work, the long-term variations of the simulated f0F2 by the NCAR thermosphere ionosphere-electrodynamics generalcirculation model (TIE-GCM) at the northern tropical crest of ionization at Phu Thuy, Hanoi, Vietnam (geographic latitudes21.030N and longitude: 105.950E) during the period from 1962 to 2002 are examined to evaluate the ability of this model toreproduce the major features of the f0F2 as observed. The TIE-GCM simulates the influences of migrating and non-migrating diurnaland semidiurnal tides at the lower thermosphere, and changes of geomagnetic activity on the long-term variations of the f0F2. Itreproduces well the diurnal and seasonal variations. We analyze the diurnal and seasonal variations of the observed f0F2 at Phu Thuyin approximately the same solar activity condition as in 1964, 1996 for the March and September equinoxes and June and Decembersolstices. The local time and seasonal structures of these simulated results correspond well to those that are observed in 1964. On thecontrary, the TIE-GCM does not reproduce the amplitude observed at Phu Thuy in 1996. The TIE-GCM with the chosen inputs doesnot yet allow us to explain well the long-term variations observed at Phu Thuy. We also try the different numerical simulations tounderstand how the long-term variations of the f0F2 is formed, how it relates to the current global system and its relationship withthe thermosphere wind. The simulations show that the calculated NmF2 values are lower than the observed values. We find that themodeled contributions of the migrating and non-migrating diurnal and semidiurnal tides may cause them to play a major role inreducing the amplitude of the NmF2. The contributions of the integrated hemispheric power of auroral electrons and the cross polarcap potential seem to play an important role in increasing the amplitude of the NmF2.References Aikin, A.C., Chanin, M.L., Nash, J., Kendig, D.J., 1991: Temperature trends in the lower mesosphere, Geophys. Res. Let., 18 (3), 416-419. Blanc, M., Richmond, A.D., 1980: The ionospheric disturbance dynamo, J. Geophys. Res., 85, 1669. Clilverd, M.A., Clark, T.D.G., Clarke, E., Rishbeth, H., 1998: Increased magnetic storm activity from 1868 to 1995, J. Atmos. Solar-Terr. Phys., Vol. 60, pp. 1047-1056. Cnossen, I., Richmond, A.D., Wiltberger, M., Wang, W., Schmitt, P., 2011: The response of the coupled magnetosphere-ionosphere-thermosphere  system to a 25% reduction in the dipole moment of the Earth’s  magnetic field, J. Geophys. Res., in press. Elias, A.G., de Artigas, M.Z., de Haro Barbas, B.F., 2010: Trends  in  the  solar  quiet geomagnetic field variation linked to the Earth’s magnetic field secular variation and increasing concentrations of greenhouse gases, J. Geophys. Res., Vol. 115, No. 8, A08316, doi: 10.1029/2009JA015136. Hagan M.E. Forbes, J.M., 2002: Migrating and non migrating diurnal tides in the middle and upper  atmosphere excited by tropospheric latent heat release, J. Geophys. Res., 107, D24, 4754. Hagan M.E., Forbes, J.M., 2003: Migrating and non migrating semidiurnal tides in the upper atmosphere excited by tropospheric latent heat release, J. Geophys. Res., 108, A2, 1062. Heelis, R.A., Lowell, J.K.,, Spiro, R.W., 1982: A model of the high-latitude ionospheric convection pattern, J. Geophys. Res., 87, 6339-6345. Huang, Y.-N., Cheng, K., Chen, S.-W, 1989: On the equatorial anomaly of the ionospheric total  electron content near the northern anomaly crest region, J. Geophys. Res.: Space physics 94 (A10), 13515–13525. Jarvis, M.J., Jenkins, B., Rodgers, G.A., 1998: Southern hermisphere observations of a long-term decrease in F region altitude and thermospheric wind providing possible evidence for global thermospheric cooling, J. Geophys. Res., 103 (A9), 20775-20778. Le Huy M., Amory-Mazaudier C., 2005: Magnetic signature of the ionospheric disturbance dynamo at equatorial latitudes: ‘‘Ddyn’’, J. Geophys. Res., vol. 110, A10301, doi:10.1029/2004JA010578. Le Huy M., Amory-Mazaudier C., 2008: Planetary magnetic signature of the storm wind disturbance dynamo currents: Ddyn, J. Geophys. Res., vol. 113, A02312, doi:10.1029/2007JA012686. Macmillan, S., Droujinina, A., 2007: Long-term trends in geomagnetic daily variation, Earth Planets Space, Vol. 59, pp. 391-195. Menvielle M., Berthelier, A., 1992: The K-derived planetary indices: description and availability, Geophys. Space Phys., 30, 91. Menvielle M., Marchaudon, A., 2006: Geomagnetic indices, in Solar-Terrestrial Physics and Space Weather in Space Weather, J. Lilensten (ed), Spr., 277-288, 2006. Menvielle M., Iyemori, T., Marchaudon, A.,  Nosé, M., 2011: Geomagnetic indices, in Geomagnetic Observations and Models, M. Mandea, M. Korte (eds), IAGA Special Sopron Book Series 5, DOI 10.1007/978-90-481-9858-0_8,  Spr. Pham Thi Thu, H., Amory-Mazaudier, C.,  Le Huy M.,  2011: Time variations of the Ionosphere at the northern tropical crest of ionization at Phu Thuy-Vietnam, Ann. Geophys., 29, pp. 197-297. Quian, L., Burns, A.G., Solomon, S.C., Roble, R.G., 2009: The effect of carbon dioxide cooling on trends in the F2-layer ionosphere, J. Atmos. Solar-Terr. Phys., Vol. 71, pp. 1592-1601. Richmond, A.D., Ridley, E.C.,  Roble, R.G., 1992: A thermosphere/ ionosphere general circulation model with coupled electrodynamics, Geophys. Res. Let., 19(6), 601-604. Richmond, A.D., 1995: Ionospheric electrodynamics using Magnetic Apex coordinates, J. Geomagn. Geoelectr., 47, 191-212. Rishbeth, H., Garriott, O.K., 1969: Introduction to Ionospheric Physics, International Geophysics series, Acad. Pres., New York and London, volume 14. Roble, R.G., 1995: Major greenhouse cooling (yes, cooling): The upper atmosphere response to increased CO2, Reviews of Geophysics, 33, 539-546. Stamper, R., Lockwood, M., Wild, M. N, Clark, T.D.G., 1999: Solar causes of the long-term increase in geomagnetic activity, J. Geophys. Res., Vol. 104, pp. 28325-28342. Ulich, T., Turunen, E., 1997: Evidence for long-term cooling of the upper atmosphere in ionosonde data, Geophys. Res. Let., 24(9), 1103-1106.